Management Accounting Practices in Cooperatives in Nepal - Subedi, Santosh (JMC Research Journal, 2022)
The present research was carried out on management accounting practices in cooperatives in Narayangarh city with the aim to examine the practices of management accounting in cooperatives. The study is based on mainly primary data which were gathered through direct interviews, questionnaires, and focus group discussions. Only eight cooperatives were chosen as samples for the research study using the judgmental method. The research was analyzed with inferential analysis including simple percentages and chi-square test. The research found out the practice of management accounting like capital budgeting, ratio analysis, activity-based budgeting, and break-even analysis is mostly used in cooperatives. Likewise, segregation of cost, cash flow statement analysis, zero-based budgeting, pricing decisions, and responsibility accounting are the least in practice in Nepalese cooperatives. The cause of non-practicing standard costing is not applicable to service industries like the financial sector. In Nepalese cooperatives, hiring an expert from outside to carry out different managerial activities is almost nil. It is concluded that Nepalese Cooperatives are in the initial state with respect to the application of modern managerial accounting tools and yet they are trying to adopt such tools and techniques more and more to cope with the future expected opportunities and challenges to face due to the globalization effect.